(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The study aimed to identify the impact of administrative leadership styles on project performance in construction projects in Riyadh. A simple random sample of (280) individuals was selected from the study community. The researcher distributed (280) questionnaires to these companies, and (250) questionnaires were retrieved, i.e. (89%) of the original distributed ones. (38) questionnaires were excluded for not meeting the conditions, including not filling out the questionnaire correctly, or a shortage in the number of questionnaire sheets. Accordingly, the number of retrieved questionnaires that were analyzed amounted to (212) questionnaires, representing (77%) of the distributed questionnaires. The study adopted the descriptive analytical approach. The results of the study concluded that there is a positive impact of administrative leadership styles (transformational and exchange) on project performance in construction projects in Riyadh, and that the most influential administrative leadership styles are the transformational leadership style, followed by the exchange leadership style, while no effect was shown for the free leadership style. The study recommended the need to focus on positive communication between the leader and the subordinate and to meet their logical and friendly needs based on love and belonging to common and mutual interests only, and to develop the skills of subordinates, whether leadership or otherwise, in exchanging ideas, adopting suggestions and participating in logical discussion.